Women's Leadership in the Indonesian Constitutional System and Islamic Law - Erwin Syahruddin; Rohman, Adi Nur (Al-Mazaahib: Jurnal Perbandingan Hukum, 2025)
This research elaborates on the power politics prevailing in Indonesia regarding women's leadership in the public sphere in Indonesia. Without realizing it, the patriarchal culture that lives in society makes women marginalized so that women are often neglected, including their rights in public leadership. This research utilizes a phenomenological approach to give meaning to the phenomenon of women's leadership in the public sphere. In addition, the legislative approach is also presented to capture and analyze regulations that open and close access for women in the public sphere. This article concludes that a woman is someone who has the right to organize and influence or organize society to achieve the goals of a country. The existence of several regulations in Indonesia that open space for women to take part in public leadership makes Indonesia an egalitarian country that provides equal and balanced rights for men and women to occupy strategic positions in the public sphere. This research found that women have the right to leadership in the public sphere just like men. Likewise, in the discourse of Islamic law, leadership is not monopolized by men but women can fill it as well as men. Penelitian ini mengelaborasi politik kekuasaan yang berlaku di Indonesia terkait kepemimpinan perempuan di ranah publik di Indonesia. Tanpa disadari, budaya patriarki yang hidup di masyarakat menjadikan perempuan termarginalkan sehingga perempuan seringkali terabaikan hak-haknya termasuk hak dalam kepemimpinan publik. Penelitian ini menginstrumentasikan pendekatan fenomenologi yang hendak memberikan makna terhadap fenomena kepemimpinan perempuan di ranah publik. Disamping itu, pendekatan perundang-undangan juga dihadirkan guna memotret dan menganalisis peraturan-peraturan yang membuka dan menutup akses bagi perempuan di ranah publik. Artikel ini menyimpulkan bahwa perempuan adalah seseorang yang berhak untuk mengatur dan mempengaruhi atau mengatur masyarakat untuk mencapai tujuan suatu negara. Adanya beberapa peraturan di Indonesia yang membuka ruang bagi perempuan untuk andil dalam kepemimpinan publik menjadikan Indonesia sebagai negara egaliter yang memberikan hak yang sama dan seimbang bagi laki-laki dan perempuan untuk menduduki posisi strategis di ranah publik. Penelitian ini menemukan bahwa perempuan memiliki hak kepemimpinan di ruang publik seperti halnya laki-laki. Begitupun dalam diskursus hukum Islam, kepemimpinan tidak dimonopoli kaum laki-laki namun perempuan bisa mengisinya juga sebaimana laki-laki.